Effect of Single Complimentary Split Ring Resonator Structure on Microstrip Patch Antenna Design - Nornikman, H; Othman, A. R.; Ahmad, B. H.; Abd Aziz, M. Z. A. (2012)
This paper had been comparing the performance of the normal patch antenna with single complimentary SRR patch antenna. Four different shapes of single complimentary split ring resonator structure had been incorporated into the microstrip patch antenna - square, circular, triangular, and rhombic. This simulation works had been done in CST Microwave Studio simulation software. The operating frequency of this antenna is 2.40 GHz for Wireless Local Area Network (WLAN) application.The parameters that considered in these works are return loss,resonant frequency, input impedance, gain, radiation pattern and bandwidth. The focusing parameter is to achieve the best gain performance that obtained from the single complimentary split ring resonator patch antenna. The addition of square SRR onto patch antenna will improve the gain from 6.334 dB to 6.508 dB.